Biological versus Topological Domains in Improving the Reliability of Evolutionary-Based Protein Complex Detection Algorithms - Abdulateef, Isra H.; Attea, Bara'a Ali; Alzubaydi, Dhia A. (Iraqi Journal of Science, 2024)
By definition, the detection of protein complexes that form protein-protein interaction networks (PPINs) is an NP-hard problem. Evolutionary algorithms (EAs), as global search methods, are proven in the literature to be more successful than greedy methods in detecting protein complexes. However, the design of most of these EA-based approaches relies on the topological information of the proteins in the PPIN. Biological information, as a key resource for molecular profiles, on the other hand, acquired a little interest in the design of the components in these EA-based methods. The main aim of this paper is to redesign two operators in the EA based on the functional domain rather than the graph topological domain. The perturbation mechanism of both crossover and mutation operators is designed based on the direct gene ontology annotations and Jaccard similarity coefficients for the proteins. The results on yeast Saccharomyces cerevisiae PPIN provide a useful perspective that the functional domain of the proteins, as compared with the topological domain, is more consistent with the true information reported in the Munich Information Center for Protein Sequence (MIPS) catalog. The evaluation at both complex and protein levels reveals that feeding the components of the EA with biological information will imply more accurate complex structures, whereas topological information may mislead the algorithm towards a faulty structure.